SIKAP MASYARAKAT DI DESA BATU BUSUK, SUMATERA BARAT TERHADAP KONSERVASI HARIMAU SUMATERA (PANTHERA TIGRIS SUMATRAE) BERDASARKAN PENGETAHUANNYA - Suryanda, Ade; Komala, Ratna; Rahmawati, Suci (Biosfer: Jurnal Pendidikan Biologi, 2017)
Sumatran tiger are one of the potential biodiversity populations which continue to decline. One of the few causes of this can occur because of human activities and actions unfavorable to the environment. Therefore, people need to have an attitude of conservation of Sumatran tiger. One of the factors that influence the attitude is knowledge. The study aims to determine the correlation between knowledge with the attitude of the Sumatran tiger conservation. The research was conducted in the village of Batu busuk, West Sumatra in May 2016. The method used was survey method with correlational studies. Data was normally distributed and homogeneous. The simple regression equation is Å¶ = 110,936 + 0.414X. Correlation coefficient obtained is 0,14 which means that there is a correlation between knowledge and towards Sumatran tiger conservation. Knowledge of Sumatran tiger conservation accounted for 1,92% of the behavior towards Sumatran tiger conservation. The result of this study concluded that there was positive correlation between knowledge and attitude of Sumatran tiger conservation.